From Cash In to Out of Cash: The Horror, Coping, and Hope of 2019 Ponzi Investment Scam Victims - Ponteres, Alexa C.; Cuambot, Ma. Ysabelle S.; Pimentel, Chino Anthony N.; Sucayan, Antonette J.; Aprecia, John Christian; Marundan, Wyatt Jayson Paul D.; Kamsa, Al-Ashier James T.; Gaygay Jr. , Carlos Friales (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This descriptive qualitative study looked into the experiences of scam investment victims in South Cotabato during 2019. Eight (8) participants who had partaken in investment fraud with a minimum age of 22 were selected through purposive and snowball sampling. Data were collected using semi-structured interviews and thematic analysis of Braun and Clarke (2006) to further understand the victim’s experiences in scam investment. In accordance with the research protocols, researchers made sure that the victims were not forced to partake in the study and their identity is confidential. Findings revealed that victims were mostly lured due to the high-return promises and framing effects. Social influence also further fuelled their desire to take part in the investment as their trusted friends and family members have shown successful gains. Fraudsters have also provided perceived legitimate evidence through mentions of registered permits. The emotional impact included disappointment, regret, and a sense of betrayal. The victim’s coping mechanisms involved optimization of resources, diverting loss to productivity, and developing a positive growth mindset, finding emotional support and optimizing strategies for them to eventually recover their losses. This study emphasized the importance of the critical need for financial literacy education, particularly regarding high-risk investments. Highlighting the importance of critical evaluation and due diligence in investment decisions. Furthermore, the government and non-state institutions, such as cooperatives and banks, initiate promoting financial awareness within communities, which are crucial to mitigating the risks of investment scams and empowering individuals to make sound decisions.